2019
DOI: 10.1111/tpj.14544
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear transporter SAD2 plays a role in calcium‐ and H2O2‐mediated cell death in Arabidopsis

Abstract: Summary In response to pathogens, plant cells exhibit a rapid increase in the intracellular calcium concentration and a burst of reactive oxygen species (ROS). The cytosolic increase in Ca2+ and the accumulation of ROS are critical for inducing programmed cell death (PCD), but the molecular mechanism is not fully understood. We screened an Arabidopsis mutant, sad2‐5, which harbours a T‐DNA insertion in the 18th exon of the importin beta‐like gene, SAD2. The H2O2‐induced increase in the [Ca2+]cyt of the sad2‐5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…The FB1 sensitivity of sad2-5 is partially dependent on Ca 2+ signaling (Zheng et al, 2019). SAD2-mediated Ca 2+ and ROS signaling appear to function downstream of LCB, since the sad2-5 fbr11-1 double mutant exhibited the same FB1-insensitive phenotype as fbr11-1 (Zheng et al, 2019). In fact, many signaling pathways involved in regulating FB1-induced cell death are associated with ROS.…”
Section: Mpk6 Ca 2+ Reactive Oxygen Species and Atp Signalingmentioning
confidence: 96%
See 2 more Smart Citations
“…The FB1 sensitivity of sad2-5 is partially dependent on Ca 2+ signaling (Zheng et al, 2019). SAD2-mediated Ca 2+ and ROS signaling appear to function downstream of LCB, since the sad2-5 fbr11-1 double mutant exhibited the same FB1-insensitive phenotype as fbr11-1 (Zheng et al, 2019). In fact, many signaling pathways involved in regulating FB1-induced cell death are associated with ROS.…”
Section: Mpk6 Ca 2+ Reactive Oxygen Species and Atp Signalingmentioning
confidence: 96%
“…The cytosolic increase in Ca 2+ levels and the accumulation of ROS are critical for inducing PCD. The disruption of Arabidopsis super sensitive to aba and drought 2 (SAD2) (an importin beta-like gene) enhanced H 2 O 2 accumulation and cell death in the sad2-5 mutant under FB1 treatment (Zheng et al, 2019). The FB1 sensitivity of sad2-5 is partially dependent on Ca 2+ signaling (Zheng et al, 2019).…”
Section: Mpk6 Ca 2+ Reactive Oxygen Species and Atp Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis , a mutation in the nuclear transporter SAD2 (sensitive to ABA and drought 2) is responsible for H 2 O 2 -induced cytosolic Ca 2+ increase. Further research showed that SAD2 works downstream of FBR11 (fumonisin B1-resistant 11) and plays a role in Ca 2+ - and H 2 O 2 -mediated cell death [ 6 ]. Recently, H 2 O 2 sensor LRR receptor kinase HPCA1 (hydrogen peroxide-induced Ca 2+ increase 1) has been demonstrated to mediate H 2 O 2 -induced activation of Ca 2+ channels in guard cells [ 152 ].…”
Section: The Role Of Ca 2+ In Pcdmentioning
confidence: 99%
“…It is reported that calcium (Ca 2+ ), a universal second messenger, is critical for PCD in plants [ 6 ]. Transient changes in cytosolic Ca 2+ level are rapidly induced by diverse stimuli in plants [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%